2018
DOI: 10.1002/jrs.5340
|View full text |Cite
|
Sign up to set email alerts
|

Plagioclase composition by Raman spectroscopy

Abstract: Plagioclase undergoes complex exsolution and ordering and phase transition processes during their evolution in nature, and this has hindered attempts to define simple trends relating the major peaks of their Raman spectra with composition. Here, the peak position and linewidth of major Raman features have been calibrated for a set of 20 plagioclases, spanning from albite to anorthite in composition, with symmetry and ordering states that were already well characterized. Point group symmetry is the most importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 37 publications
(72 reference statements)
4
58
0
Order By: Relevance
“…The strongest peaks in plagioclase are found at 478 and 507 cm −1 ( ν b and ν a ). The ν a peak is modified less by changing Al—Si order, but more with composition . It is therefore most suitable to assess the compositional changes in plagioclase.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The strongest peaks in plagioclase are found at 478 and 507 cm −1 ( ν b and ν a ). The ν a peak is modified less by changing Al—Si order, but more with composition . It is therefore most suitable to assess the compositional changes in plagioclase.…”
Section: Discussionmentioning
confidence: 99%
“…The ν a peak is modified less by changing Al-Si order, but more with composition. [6,28] It is therefore most suitable to assess the compositional changes in plagioclase. On the other hand, the peaks ν c and ν b are most suitable to determine the degree of Al-Si order in a given feldspar.…”
Section: Implications and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bersani and co‐workers reported plagioclase composition by Raman spectroscopy. They found that the Raman compositional results for a plagioclase from Marsili submarine volcano agree with composition and zoning found from analysis by laser ablation . Dufresne et al measured the Raman spectra of the eight natural carbonate minerals of calcite structure and analyzed the results using a model based on a graphical approach .…”
Section: Solid‐state Studiesmentioning
confidence: 80%
“…By means of this approximation, the deviation of the measurements in intermediate plagioclases is estimated to be up to 10%. To determine more accurately the composition of the sintered glass–ceramic, the peaks width and positions of the Raman spectra are compared with some plagioclases with different content of anorthite reported in the literature . Thus, from a mineralogical point of view, the composition of the fast‐sintered glass–ceramic is placed between an oligoclase (~An25) and an andesine (~An45) .…”
Section: Resultsmentioning
confidence: 99%